2008
DOI: 10.1002/ana.21375
|View full text |Cite
|
Sign up to set email alerts
|

Predicting progression in primary progressive multiple sclerosis: A 10‐year multicenter study

Abstract: Rates of progression vary widely in primary progressive multiple sclerosis. This multicenter study aimed to identify predictors of progression over 10 years. A total of 101 patients who had been imaged at baseline and 2 years were scored on the expanded disability status scale after 10 years. Ordinal logistic regression identified the following independent variables that predicted progression: male sex, shorter disease duration, and slower timed walk test at baseline (best overall predictor), and deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 19 publications
6
86
3
2
Order By: Relevance
“…4, significant increases and decreases in magnetization transfer across time can be used to assess remyelination and demyelination [18,19]. As in other MS subtypes, cerebral MTR values are decreased in PPMS patients relative to controls [22,41,42,69]. Comparisons of MTR values between groups of PPMS and RRMS patients have not found significant differences [23].…”
Section: Imaging Findings In Ppmsmentioning
confidence: 99%
“…4, significant increases and decreases in magnetization transfer across time can be used to assess remyelination and demyelination [18,19]. As in other MS subtypes, cerebral MTR values are decreased in PPMS patients relative to controls [22,41,42,69]. Comparisons of MTR values between groups of PPMS and RRMS patients have not found significant differences [23].…”
Section: Imaging Findings In Ppmsmentioning
confidence: 99%
“…Measures provided by diffusion tensor imaging and 1 H-magnetic resonance spectroscopy ( 1 H-MRS), have been shown to correlate with disability (SastreGarriga et al, 2005;Ramio-Torrenta et al, 2006;Bodini et al, 2013) and predict progression (Khaleeli et al, 2007(Khaleeli et al, , 2008. Applying similar techniques to the spinal cord has been technically challenging .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although sex has a less dramatic effect on disease progression and clinical outcomes, several studies have reported more severe symptoms and faster progression in men. [4][5][6][7] The underlying processes thought to be involved in the development and progression of MS demonstrate significant sex differences. For example, male and female patients with MS have shown differences in the markers of autoimmune function, [8][9][10] and there has been extensive research on the effects of sex hormones on disease progression, particularly during and after pregnancy.…”
mentioning
confidence: 99%